Dysbalance of Astrocyte Calcium under Hyperammonemic Conditions - Haack, Nicole; Dublin, Pavel; Rose, Christine R. (PLOS ONE, 2014)
Increased brain ammonium (NH4+/NH3) plays a central role in the manifestation of hepatic encephalopathy (HE), a complex syndrome associated with neurological and psychiatric alterations, which is primarily a disorder of astrocytes. Here, we analysed the influence of NH4+/NH3 on the calcium concentration of astrocytes in situ and studied the underlying mechanisms of NH4+/NH3-evoked calcium changes, employing fluorescence imaging with Fura-2 in acute tissue slices derived from different regions of the mouse brain. In the hippocampal stratum radiatum, perfusion with 5 mM NH4+/NH3 for 30 minutes caused a transient calcium increase in about 40% of astrocytes lasting about 10 minutes. Furthermore, the vast majority of astrocytes (∼90%) experienced a persistent calcium increase by ∼50 nM. This persistent increase was already evoked at concentrations of 1–2 mM NH4+/NH3, developed within 10–20 minutes and was maintained as long as the NH4+/NH3 was present. Qualitatively similar changes were observed in astrocytes of different neocortical regions as well as in cerebellar Bergmann glia. Inhibition of glutamine synthetase resulted in significantly larger calcium increases in response to NH4+/NH3, indicating that glutamine accumulation was not a primary cause. Calcium increases were not mimicked by changes in intracellular pH. Pharmacological inhibition of voltage-gated sodium channels, sodium-potassium-chloride-cotransporters (NKCC), the reverse mode of sodium/calcium exchange (NCX), AMPA- or mGluR5-receptors did not dampen NH4+/NH3-induced calcium increases. They were, however, significantly reduced by inhibition of NMDA receptors and depletion of intracellular calcium stores. Taken together, our measurements show that sustained exposure to NH4+/NH3 causes a sustained increase in intracellular calcium in astrocytes in situ, which is partly dependent on NMDA receptor activation and on release of calcium from intracellular stores. Our study furthermore suggests that dysbalance of astrocyte calcium homeostasis under hyperammonemic conditions is a widespread phenomenon, which might contribute to the disturbance of neurotransmission during HE.